TechnoLogics : ghosts, the incalculable, and the suspension of animation - Kochhar-Lindgren, Gray (State University of New York Press, 2005)
"Adding to the growing field of posthuman or cyborg studies, TechnoLogics explores how our position in the technologized world reorders, in the most radical ways imaginable, our basic experience of the lines governing literary, philosophical, and cultural production. The ancient dream of immortality is now becoming realized through cloning, genetic research, and artificial intelligence, bringing with it the need for new forms of both reading and living in the everyday world. In this emerging cyborg culture, what is to come for us is not predictable but, instead, an open possibility to be shaped by the work of, among others, artists, computer designers, scientists, and writers. Through encounters with Plato, Melville, Marx, Junger, Heidegger, Freud, Derrida, Baudrillard, and others, Gray Kochhar-Lindgren identifies the causes, characteristics, and links between the most primordial of wishes - immortality - and the highest of high tech, and asks how, in our culture of technocapitalism, we can continue to listen to the faint call of ethics."--Jacket
Keywords: Technology -- Social aspects.; SCIENCE -- Philosophy & Social Aspects.; TECHNOLOGY & ENGINEERING -- Social Aspects.; Technology -- Social aspects